2014
DOI: 10.1371/journal.pone.0106624
|View full text |Cite
|
Sign up to set email alerts
|

The Association between DNA Copy Number Aberrations at Chromosome 5q22 and Gastric Cancer

Abstract: BackgroundGastric cancer is common cancer. Discovering novel genetic biomarkers might help to identify high-risk individuals. Copy number variation (CNV) has recently been shown to influence risk for several cancers. The aim of the present study was sought to test the association between copy number at a variant region and GC.MethodsA total of 110 gastric cancer patients and 325 healthy volunteers were enrolled in this study. We searched for a CNV and found a CNV (Variation 7468) containing part of the APC gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…52 Its protein product negatively regulates WNT signaling and its inactivation leads to β-catenin accumulation and transcriptional activation of genes (MYC, cyclin D1) related to cell proliferation. 53,54 As reported, the chromosome locus of APC is frequently deleted in GCs, [55][56][57][58][59] and its decreased copy number significantly associated with lymph node invasion and metastasis in GC patients. 55 Moreover, APC deletion was principally found in advanced GCs, suggesting that it might be involved in the progression but not initiation of GCs.…”
Section: Chromosomementioning
confidence: 75%
See 1 more Smart Citation
“…52 Its protein product negatively regulates WNT signaling and its inactivation leads to β-catenin accumulation and transcriptional activation of genes (MYC, cyclin D1) related to cell proliferation. 53,54 As reported, the chromosome locus of APC is frequently deleted in GCs, [55][56][57][58][59] and its decreased copy number significantly associated with lymph node invasion and metastasis in GC patients. 55 Moreover, APC deletion was principally found in advanced GCs, suggesting that it might be involved in the progression but not initiation of GCs.…”
Section: Chromosomementioning
confidence: 75%
“…53,54 As reported, the chromosome locus of APC is frequently deleted in GCs, [55][56][57][58][59] and its decreased copy number significantly associated with lymph node invasion and metastasis in GC patients. 55 Moreover, APC deletion was principally found in advanced GCs, suggesting that it might be involved in the progression but not initiation of GCs. Furthermore, in a study concerning 131 sporadic gastric adenocarcinoma samples with matched normal tissues, Fang et al 60 demonstrated APC copy number deletions were found in a relatively high percentage (25.9%) and were associated with lymph node invasion or metastasis of GC.…”
Section: Chromosomementioning
confidence: 75%
“…However, we have found one report on CNVs associated with gastric cancer. Tsai et al reported that a loss of a CNV at 5q22 including APC-exon 9 gives rise to a high risk of the disease [50].…”
Section: Gastric Cancermentioning
confidence: 99%
“…). Other acquired abnormalities were a gain of the long arm of chromosome 6 and deletion of the APC gene previously reported in solid tumors (Table S1). The patient was treated with polychemotherapy (prednisone, vincristine, daunorubicin, cyclophosphamide, and l ‐asparaginase) and addition of the anti‐JAK2 drug ruxolitinib (2 × 10 mg/day) allowing the achievement of complete remission.…”
Section: Case Historymentioning
confidence: 88%